Posterior Idiopathic Fascicular Ventricular Tachycardia. A Case Report - Gilberto Cairo Sáez; Carlos Javier Moya Moya; Álvaro Javier Escalante Castellón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Idiopathic fascicular ventricular tachycardia is rare. It usually occurs in young patients or children. We present the case of a 57 years old female patient with no previous cardiovascular disease. The patient started having a sudden installation tachycardia and right bundle branch block with axis deviation to the left, which responded to the administration of verapamil. Posterior idiopathic fascicular ventricular tachycardia was diagnosed. The main interest in this case is the disease onset age which demonstrates the need for a high index of suspicion when electrocardiographic pattern is presented, regardless of patient age.